Cucurbit [8] uril-based supramolecular fluorescent biomaterials for cytotoxicity and imaging studies of kidney cells - Xiao, Han; Yang, Xia; Yang, Li; Yang, Dan; Luo, Yang; Yang, Hai-Ping; Tao, Zhu; Xiao, Xin; Li, Qiu (Frontiers in Chemistry, 2022)
An accurate diagnosis of acute kidney injury (AKI) at the early-stage is critical to not only allow preventative treatments in time but also forecast probable medication toxicity for preventing AKI from starting and progressing to severe kidney damage and death. Therefore, supramolecular fluorescent biomaterials based on Q[8] and PEG-APTS have been prepared herein. This study has found that the unique properties of outer surface methine and positive charge of Q[8] can form a stable assembly with PEG-APTS, and has provided the possibility for the faster crossing of the glomerular filtration barrier to enter into the resident cells of kidney. In addition to the excellent fluorescence properties, the as-synthesized biomaterial Q[8]@PEG-APTS has possessed significantly low biological toxicity. Most importantly, the accumulation of Q[8]@PEG-APTS in large amounts in cytoplasm and nucleus of HK2 and HMCs cells, respectively, within 24 h enabled distinguishing kidney cells when diagnosing and providing some foundation for early AKI.